2017
DOI: 10.1139/bcb-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactoferrin in 6 patients with refractory bacterial vaginosis

Abstract: We previously reported that lactoferrin (LF) could be effective for preventing preterm delivery and intrauterine infections, based on data derived from mice and rabbits. Here we describe 6 women with a history of multiple pregnancy losses or preterm delivery and refractory bacterial vaginosis, who received prebiotic LF therapy and delivered an infant normally. Five of the women were pregnant and one was not at the time of this study. The Ethics Committee at Showa University Hospital and Showa University Koto T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…Lactoferrin, at two different concentrations (100 mg and 200 mg), was administered to women with BV and its ability to modify the vaginal bacterial biota, both during and after administration, was studied in depth. The results demonstrated that both concentrations significantly increased the level of lactobacilli and decreased pathogenic bacteria such as Gardnerella , Prevotella , and Lachnospira during the treatment, in accordance with previous studies [31,33]. Differences were detected 2 weeks after administration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lactoferrin, at two different concentrations (100 mg and 200 mg), was administered to women with BV and its ability to modify the vaginal bacterial biota, both during and after administration, was studied in depth. The results demonstrated that both concentrations significantly increased the level of lactobacilli and decreased pathogenic bacteria such as Gardnerella , Prevotella , and Lachnospira during the treatment, in accordance with previous studies [31,33]. Differences were detected 2 weeks after administration.…”
Section: Discussionsupporting
confidence: 91%
“…All the women underwent a complete assessment in three scheduled appointments: at baseline (T0), on the 10th day of treatment (treatment: T1), and 2 weeks after the end of lactoferrin administration (post-treatment: T2). Inclusion criteria were sexually active women of reproductive age (18–45 years old) with regular menstrual cycles and with symptomatic acute BV diagnosed according to Amsel’s criteria [33] and Nugent score [34]. The exclusion criteria were age < 18 years; Nugent score < 7; known active infection due to Chlamydia , yeasts, Neisseria gonorrhoeae , or Trichomonas vaginalis ; clinically apparent herpes simplex infection or defined diagnosed human papillomavirus, herpes simplex virus type 2, or human immunodeficiency virus type 1 infection; pregnancy or breastfeeding; antibiotic, probiotic, or exogenous hormone treatments; and other gynecological conditions that could cause bleeding (polyps, endometrial hyperplasia, etc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin is a glycoprotein involved in the host protection against pathogen microorganisms, such as bacteria, viruses and yeasts, and its levels in vaginal secretions increase significantly during infections such as gonorrhoea, Chlamydia , cervicitis, bacterial vaginosis and trichomoniasis thus highlighting its protective physiological role against pathogens and inflammation. Moreover, both the oral and vaginal administration of lactoferrin have been proven to improve the vaginal microbiota composition by increasing the number of lactobacilli, which contribute to hamper pathogen growth . Evidence shows that it is able to reduce significantly the growth of Candida albicans and C. glabrata .…”
Section: Discussionmentioning
confidence: 99%
“…Otsuki and Imai (2017) report that treatment of 6 women at high risk of preterm delivery with bovine Lf (bLf) significantly improved the vaginal microflora, and Sessa et al (2017) report that intravaginal administration of bLf resolved asymptomatic Chlamydia trachomatis in 6 of 7 pregnant women. All of the women treated with bLf in both studies had normal deliveries.…”
Section: Introductionmentioning
confidence: 99%